PERLINDUNGAN HUKUM PIHAK KETIGA TERHADAP KETIADAAN PUBLISITAS AKTA FIRMA BERDASARKAN KUHD - Afifah Zahirah Fatra; Zauwana Fitri Ahyuni; Khairunnisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
A firm (firma), as a non-legal-entity business association, is subject to deed publicity under Articles 22, 23, 28, and 29 of the Indonesian Commercial Code (KUHD). This study examines how the absence of registration and announcement affects the legal position of a firm and the protection of good-faith third parties. It applies normative legal research using statutory and conceptual approaches to the KUHD, Government Regulation Number 28 of 2025, Minister of Law Regulation Number 25 of 2025, and relevant legal doctrine. The analysis shows that Article 29 KUHD allocates the information risk to the non-compliant firm: vis-à-vis third parties, the firm is deemed general in scope, established for an indefinite period, and every partner is deemed authorized to act on its behalf. Internal restrictions that were not publicized therefore cannot readily be asserted against third parties. This mechanism provides repressive protection after a dispute arises, but it does not fully provide preventive protection before a transaction. The current electronic registration regime strengthens administrative recording, yet accessible and up-to-date publicity remains essential so that third parties can verify the identity and authority of partners. The legal protection model should consequently combine the consequences under Article 29 KUHD with an accessible public register and clearer administrative compliance mechanisms.